1994
DOI: 10.1183/09031936.94.07010186
|View full text |Cite
|
Sign up to set email alerts
|

Serum tumour markers in lung cancer: history, biology and clinical applications

Abstract: S Se er ru um m t tu um mo ou ur r m ma ar rk ke er rs s i in n l lu un ng g c ca an nc ce er r: : h hi is st to or ry y, , b bi io ol lo og gy y a an nd d c cl li in ni ic ca al l a ap pp pl li ic ca at ti io on ns s Several tumour markers have been studied in lung cancer. Unfortunately, none of these appear to be sufficiently sensitive and specific to be reliable for screening and diagnostic purposes. However, there is a body of evidence which proves that at least some of these substances may be useful in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
2
5

Year Published

1995
1995
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 130 publications
1
55
2
5
Order By: Relevance
“…Lung cancer is one of the most common malignancies in humans (Ferrigno et al 1994). The accumulation of damage at different molecular and cellular levels is the underlying mechanism of lung carcinogenesis (Finkel et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is one of the most common malignancies in humans (Ferrigno et al 1994). The accumulation of damage at different molecular and cellular levels is the underlying mechanism of lung carcinogenesis (Finkel et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Since one of the main limits of the clinical applicability of the serum tumour markers is its lack of sensitivity in the early stages (McIntire 1982;Ferrigno et al, 1994), we investigated whether any association could be observed between the rate of correct classification obtained by the score and the tumour stages. This analysis showed that stages, sex and age did not influence the error rate.…”
Section: Discussionmentioning
confidence: 99%
“…The other variables recorded were age, sex, ECOG performance status, weight loss, haemoglobin concentration, total white cell/neutrophil counts, tumour cell type, clinical stage, and the single tumour, node and metastasis factors, analysed individually for their prognostic meaning. In addition, the serum concentration of each of the following were measured and recorded: lactate dehydrogenase, alkaline phosphatase, pyruvic and oxalacetic transaminases, creatinine, sodium, carcinoembryonic antigen, and tissue polypeptide antigen [16]. Follow-up consisted of clinical, laboratory, and radiological reassessments at 3±4 week intervals during chemotherapy, and every 3±6 weeks in case of palliative radiotherapy, or no anticancer treatment.…”
Section: Methodsmentioning
confidence: 99%